The Role Of Organizational Culture In Improving Public Services At The Sukabumi Regency Tourism Office - Mansyur, Makbul (SEAN Institute, 2022)
The Sukabumi Regency Tourism Office is the focus of this investigation, and its purpose is to determine how organizational culture might contribute to the enhancement of public service. The type of study that is carried out is known as qualitative research, and the data gathering methods that are utilized include observation, interviews, and documentation. The personnel of the Sukabumi Regency Tourism Office who were directly involved in the provision of public services were the ones that participated in the research. Using qualitative analytic approaches in conjunction with the Miles and Huberman models, the collected data were evaluated and interpreted. According to the findings of the research, the organizational culture that currently exists in the Tourism Office of the Sukabumi Regency has an impact on both the level of performance and the quality of the public services that are offered. An organizational culture that is positive and has character causes employees to have high motivation and enthusiasm in providing good and satisfying public services to the community. In addition, a strong organizational culture also influences the attitudes and behavior of employees in carrying out their duties and responsibilities. This study recommends that the Sukabumi Regency Tourism Office need to improve a positive organizational culture and character by strengthening the values of honesty, professionalism, cooperation, and good public service.